Good Outcome In Open Globe Injury With Intraocular Foreign Body - Rahayu Widhyasti; Made Indra Widyanatha; Arief S. Kartasasmita; Rova Virgana; Grimaldi Ihsan; Erwin Iskandar (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2024)
Introduction: Intraocular foreign body (IOFB) represents the second most common cause of open globe injury (OGI) and critical ophthalmic emergency that requires urgent diagnosis and treatment to prevent blindness. It can cause direct damage via entry into the eye and causing future damage. The immediate pars plana vitrectomy (PPV) surgery in post-traumatic endophthalmitis is beneficial for optimizing visual prognosis. Case report: A 55-year-old male patient came to the Emergency Room tertiary referral hospital with chief complaints of blurry vision, pain, and red-eye in his right eye 3 days before admission. The patient’s right eye was hit by a fragment of the sickle knife while mowing the grass in the yard without protective eyeglasses. Painful on his right eye is getting worse accompanied by lacrimation. The patient went to Tertiary Eye Hospital because of his complaints getting worse. The patient was diagnosed with Open Globe Injury Type C grade D pupil B zone 1, suspect early endophthalmitis, traumatic cataract of the right eye, and hypertension. Pars plana vitrectomy, vitreous tap, antibiotic intravitreal injection (with Ceftazidime and Vancomycin), IOFB extraction, explore, corneal scraping on the wound, cultural resistance, primary hecting of the cornea were done. The visual acuity improves and the infection was resolved. Conclusion : One of the most common traumas in ophthalmology is IOFB and it is considered an emergency condition. Proper ophthalmology examination and appropriate ancillary testing should be done to reveal this condition. Good management will give a good result of the patient’s visual prognosis.